Analysis of Cardboard Quality Improvement Using The Taguchi Method - Yohana Siahaan; Uun Novalia Harahap; Yetti Meuthia Hasibuan (JiTEKH, 2025)
The company faces a recurring issue related to product defects, which affect both production efficiency and customer satisfaction. To address this problem, this study applies a causal and experimental research approach using the Taguchi Method as a systematic tool for process optimization and quality improvement. The Taguchi Method is employed to identify the optimal combination of process parameters that significantly influence the quality of cardboard boxes while minimizing defects and production variability. Based on the results of data processing and analysis, it can be concluded that the optimal combination of factor levels that significantly influence the improvement of carton box product quality, as determined through the Taguchi experimental design, is Speed at level 2 (280 mpm), Air Supply at level 2 (0.88 MPa), and Steam Supply at level 2 (5 MPa). These optimal conditions demonstrate the most effective balance between production efficiency and product consistency, and must be properly maintained to ensure stable and high-quality output. Furthermore, improvement efforts based on the Taguchi method emphasize the importance of the human factor or operator in sustaining these optimal settings. Operators must be trained to respond appropriately to changes in process parameters and to maintain consistent conditions during production. The results of this research confirm that the Taguchi Method provides a robust, data-driven framework for continuous improvement, helping  reduce defects, optimize process performance, and achieve sustainable quality enhancement in its cardboard manufacturing operations